2011
DOI: 10.1016/j.mrgentox.2011.01.009
|View full text |Cite
|
Sign up to set email alerts
|

When pigs fly: Immunomagnetic separation facilitates rapid determination of Pig-a mutant frequency by flow cytometric analysis

Abstract: In vivo mutation assays based on the Pig-a null phenotype, that is, the absence of cell surface glycosylphosphatidylinositol (GPI) anchored proteins such as CD59, have been described. This work has been accomplished with hematopoietic cells, most often rat peripheral blood erythrocytes (RBCs) and reticulocytes (RETs). The current report describes new sample processing procedures that dramatically increase the rate at which cells can be evaluated for GPI anchor deficiency. This new method was applied to blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 17 publications
2
106
0
2
Order By: Relevance
“…Immunomagentic methods for depletion of wild-type RBCs (Dertinger et al, 2011b) or enrichment of RETs (Kimoto et al, 2011a) show promise in this regard. Dertinger et al developed a system for depletion of CD59-positive RBCs Vol.…”
Section: Discussionmentioning
confidence: 99%
“…Immunomagentic methods for depletion of wild-type RBCs (Dertinger et al, 2011b) or enrichment of RETs (Kimoto et al, 2011a) show promise in this regard. Dertinger et al developed a system for depletion of CD59-positive RBCs Vol.…”
Section: Discussionmentioning
confidence: 99%
“…Son intérêt réside, en partie, dans les faibles volumes de sang nécessaires pour l'examen permettant ainsi des analyses itératives, par exemple sur le même animal dans les études de toxicologie à administrations réitérées. Les protocoles appliqués actuellement chez le rongeur permettent d'analyser en quelques minutes plus d'un million d'érythrocytes ou de réticulocytes à partir d'un prélèvement sanguin de 100 µl [27]. Si le principe du test reste inchangé, le protocole a progressivement été amélioré afin d'augmenter ses performances tout en limitant le nombre d'événements totaux analysés.…”
Section: éVolution De La Techniqueunclassified
“…Un champ magnétique permettra de retenir les cellules marquées fixées sur les billes. L'analyse sera réalisée soit sur les cellules retenues [4,30], soit sur les cellules non marquées, et donc libres, qui seront récupérées dans l'éluat [27].…”
Section: éVolution De La Techniqueunclassified
“…Both were incubated for 20 min. Then, the samples were washed and mixed together; thus, the mixture was able to provide sufficient numbers of RBCs, and a full range of FITC fluorescence intensities were useful for optimizing PMT voltages and fluorescence compensation settings (Dertinger et al, 2011). Moreover, the accuracy of flow cytometry detection was assessed by evaluating the linear correlation between the expected CD59-negative value and the theoretical value; the measurements were set to 1.…”
Section: Acceptable Criterionmentioning
confidence: 99%
“…The two phenotypes can be distin-guished and detected by indirect immunofluorescence staining (Kimoto et al, 2012). Presently, the Pig-a gene has been utilized successfully to investigate the MF in many studies (Bhalli et al, 2011;Dobrovolsky et al, 2012;Dertinger et al, 2011). The literature data indicated that the absence of GPI is the leading cause of paroxysmal nocturnal haemoglobinuria (PNH) (Phillips et al, 2001).…”
Section: Introductionmentioning
confidence: 99%